2014
DOI: 10.4319/lom.2014.12.390
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous bed‐sediment imaging‐systems for revealing temporal variability of grain size

Abstract: Variation in nearshore bed-sediment grain sizeNearshore sediment transport determines the fate of seabed nutrients, contaminants, and pathogens; asserts control on the seabed and water column as habitats; and drives changes in seafloor topography which, in turn, affect wave transformation processes, spatial gradients in energy dissipation, and nearshore hydrodynamic circulation patterns. Relatively small changes in grain size have been shown to change the sign (depositional or erosional) of nearshore net sand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…For its utility in field settings, especially in remote A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 or inaccessible areas or long-term deployments, the new non-calibration method facilitates the development of a fully transferable method. In addition, the "autocorrelation" approach including subsequent wavelet method has been successful in obtaining grain-size distribution and associated parameters (Buscombe and Rubin, 2012;Buscombe, 2013;Buscombe et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…For its utility in field settings, especially in remote A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 or inaccessible areas or long-term deployments, the new non-calibration method facilitates the development of a fully transferable method. In addition, the "autocorrelation" approach including subsequent wavelet method has been successful in obtaining grain-size distribution and associated parameters (Buscombe and Rubin, 2012;Buscombe, 2013;Buscombe et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Four example 1024 × 1024 pixel subsets of images from each of six population categories. From top to bottom: (1) well‐sorted gravel; (2) well‐sorted sand and shell hash from underwater camera (described in Buscombe et al , ); (3) relatively poorly sorted gravel and sand–gravel mixtures (including imagery from Warrick et al , ); (4) well‐sorted sand; (5) miscellaneous terrigenous and volcaniclastic grains; and (6) miscellaneous bioclastic (carbonate) grains. [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Datamentioning
confidence: 99%
“…White areas in (C) are due to lack of coverage in the aerial imagery. analysis can produce GSDs within 4% of those measured by sieve and settling tube (Barnard et al, 2007;Gallagher et al, 2011;Buscombe et al, 2014). However, comparative studies in bioclastic environments have suggested that sieve can yield significantly larger mean grain-size estimates (up to 300%) than settling tube for coarse samples (mean >1 mm), smaller mean grain-size estimates in fine samples (mean <1 mm; Kench & McLean, 1997), and that the relationship between sieve and settling tube can be significantly non-linear (Smith & Cheung, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…with variable shapes (rods, discs and plates) and densities (Maiklem, ; Braithwaite, ). Previous methodological comparisons using siliciclastic sediment have shown that sieve and settling tube analysis produce nearly identical GSDs when deposits are well‐sorted (Komar & Cui, ); sieve and laser diffraction analysis yield similar GSDs for sand‐sized material (Cheetham et al ., ; Di Stefano et al ., ); and image analysis can produce GSDs within 4% of those measured by sieve and settling tube (Barnard et al ., ; Gallagher et al ., ; Buscombe et al ., ). However, comparative studies in bioclastic environments have suggested that sieve can yield significantly larger mean grain‐size estimates (up to 300%) than settling tube for coarse samples (mean >1 mm), smaller mean grain‐size estimates in fine samples (mean <1 mm; Kench & McLean, ), and that the relationship between sieve and settling tube can be significantly non‐linear (Smith & Cheung, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation